A holistic assessment of greenhouse gas dynamics from forests to the effects of wood products use in Austria. Issue 5 (1st November 2016) - Braun, Martin; Fritz, David; Weiss, Peter; Braschel, Nina; Büchsenmeister, Richard; Freudenschuß, Alexandra; Gschwantner, Thomas; Jandl, Robert; Ledermann, Thomas; Neumann, Markus; Pölz, Werner; Schadauer, Klemens; et al.
ABSTRACT: Anthropogenic GHG emissions add a fast reinforcing feedback cycle to global carbon dynamics which continues to influence GHG concentrations in the Earth's atmosphere. When looking at forest carbon cycles there is potential in utilizing another feedback cycle, namely the carbon cycle involving harvested wood products. To assess the potential of the mitigation options arising from these carbon flows, the forest-based sector in Austria was modelled to assess causal links, dependencies and dynamics involved in GHG-relevant processes. Carbon dynamics were investigated in forests and forest soil carbon, the forest product chain and life-cycle analyses for substitution of conventional products with wood products in a cascade of different modelling approaches and paradigms, and the results synthesized. It was found that material use of products from domestic timber sources has the highest climate change mitigation efficiency when originating from sustainably managed forests regarding biomass stocks. The emissions saved through building up a carbon stock from harvested wood products and through emissions substitution can be as high as ∼20 years of total annual Austrian emissions in 90 years. Additional conservation measures while sustaining sawnwood production and the related GHG benefits at a high level had the highest contribution to an overall carbon sink.